DETERMINATION OF SHALE GAS POTENTIAL OF NORTH SUMATRA BASIN: AN INTEGRATION OF GEOLOGY, GEOCHEMISTRY, PETROPHYSICS AND GEOPHYSICS ANALYSIS - Junita Trivianty Musu; Bambang Widarsono; Andi Ruswandi; Himawan Sutanto; Humbang Purba (Testing Center for Oil and Gas LEMIGAS, 2015)
A detailed combined geological and geophysical study in North Sumatra basin has shown thatprospective formations for shale play containing gas sweet spots are found to be in shales from Bampo,Belumai, and Baong Formations. Bampo Formation exhibits low shale gas potential with very low tomedium in organic material contents, maturity index of immature to mature, and moderate brittleness. Rockswithin the formation tend to be reactive to highly reactive to water, with a moderate degree of swellingcapacity. Porosity varies within 5.8 - 7.4 % with permeability ranging from 0.37 to 3.2 mD. Sweet spots inthe formation found around Basilam-1 and Securai-1wells occupy about 21% of the formation. On the otherhand, Belumai Formation shows moderate to good shale gas potential, with low to high organic materialcontents, immature to mature levels of maturity, and moderately brittle to brittle. Sweet spot areas in theformation found around the two wells are about 29% of the formation. For Baong Formation, analysisreveals moderate to good shale gas potential, with low to medium contents of organic material, immatureto mature in maturity index, moderately brittle to brittle in brittleness, and tendency of being reactiveto highly reactive to water but with low degree of swelling capacity. Sweet spots in the formation foundaround the two wells occupies are roughly 11% of the total formation volume in the area. Basin modelingleading to gas resources estimation for Baong, Belumai and Bampo Formations has led to estimatedvolumes of 6,379 TCF, 16,994 TCF, and 25,024 TCF, respectively, with a total amount of 48,397 TCF.The resources figures are speculative in nature and do not incorporate any certainty and efficiency factors.